Threshold effects of institutional quality on the financial inclusion and stability nexus: International evidence - Setianto, Rahmat Heru; Azman-Saini, W. N.W.; Law, Siong Hook (Borsa Istanbul Anonim Sirketi, 2025)
This study employs the dynamic panel threshold estimation technique to examine whether the influence of financial inclusion on stability varies across countries with different levels of institutional development. This study analyzes 11,209 observations of bank-level data from 78 developed and developing countries from 2004 to 2022. The findings indicate a threshold effect in the relationship between financial inclusion and stability. Specifically, for institutional quality below the threshold, financial inclusion has an insignificant stability effect. However, after reaching a certain threshold of institutional development, the effect of financial inclusion on financial stability becomes positive and significant. These findings suggest that the impact of financial inclusion on stability is contingent on institutional quality. Enhancing institutional quality to minimize risk can enhance the stability benefits of expanding financial inclusion. These findings remain robust across alternative empirical approaches and disaggregated measures of financial inclusion and institutional quality. These findings have important implications for policymakers formulating strategies for improving financial inclusion and economic stability.